Hubungan Pengetahuan Perawat dengan Penanganan Awal Pasien Cidera Kepala di IGD RSUD M.M Dunda Limboto - Pipin Yunus; Arifin Umar; Haslinda Damansyah; Kristin Tangahu (Malahayati Nursing Journal, 2025)
ABSTRACT Head injury is a condition where there is an injury to the head which can cause damage to brain tissue due to trauma. Head injuries are the most common neurological disease among other neurological diseases which are usually caused by accidents. Handling head injuries requires good knowledge from nurses. Apart from that, age, gender, education and length of work are related to the initial treatment of head injuries. Objective: to determine the relationship between nurses' knowledge and initial treatment of head injury patients. Method: quantitative research design with analytical observational with a cross sectional approach, total population of 38 people with a total sample of 38 people or total sampling. Results: The results of the study showed that the highest knowledge of nurses was good knowledge at 34 people and the highest initial treatment for head injuries was good at 35 people with a value of pValue=0.0000.05. Conclusion: there is a relationship between nurses' knowledge and the initial treatment of head injury patients, while there is no relationship between gender and length of work of nurses in the initial treatment of head injury patients. Suggestion: for nurses to increase their knowledge by attending several trainings in handling head injuries or exchanging information with fellow nurses to increase knowledge. Keywords: Head Injury, Knowledge, Initial Treatment  ABSTRAK Cedera kepala merupakan suatu kondisi terjadinya cedera pada kepala yang dapat menyebabkan kerusakan jaringan otak akibat adanya trauma. Cedera kepala merupakan penyakit neurologis yang paling sering terjadi diantara penyakit neurologis lainnya yang biasa disebabkan oleh kecelakaan. Dalam penanganan cidera kepala membutuhkan pengetahuan yang baik dari perawat selain itu umur, jenis kelamin, pendidikan serta lama kerja berhubungan dengan penanganan awal cidera kepala. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan perawat dengan penanganan awal pasien cidera kepala. Desain penelitian kuantitatif dengan observasional analitik dengan pendekatan cross sectional, jumlah populasi sebanyak 38 orang dengan jumlah sampel sebanyak 38 orang atau total sampling. Hasil: hasil penelitian menunjukan pengetahuan perawat tertinggi yaitu pengetahuan baik sebanyak 34 orang dan penanganan awal cidera kepala yang tertinggi yaitu baik sebanyak 35 orang  dengan nilai pValue=0.0000.05. Kesimpulan: terdapat hubungan pengetahuan perawat dengan penanganan awal pasien cidera kepala sedangkan tidak terdapat hubungan jenis kelamin dan lama kerja perawat dalam penanganan awal pasien cidera kepala. Saran: untuk perawat agar dapat meningkatkan pengetahuan dengan cara mengikuti beberapa pelatihan dalam penanganan cidera kepala atau saling bertukar informasi dengan sesama perawat dalam meningkatkan pengetahuan. Kata Kunci: Cidera Kepala, Pengetahuan, Penanganan Awal